Bridging the Gap Between Gaming and Theatre: »The Dark Fortress – A Minecraft Adventure« - Knutsen, Raymond Corrado (BUKS - Tidsskrift for Børne- & Ungdomskultur, 2025)
In the Norwegian National Touring Theatre’s (Riksteatret) original production The Dark Fortress – A Minecraft Adventure, children with little or no prior experience in theatre entered a world where their gaming expertise was not only acknowledged – it was central. In my role as Game Master, I served as both guide and performer, bridging the pixelated landscapes of Minecraft with the embodied, collective space of live theatre.